Pertimbangan Hakim Dalam Putusan Mahkamah Agung Nomor 508 K/PID/2017 Terkait Tindak Pidana Penggelapan Dalam Jabatan Notaris - Uyun, Kurrotul (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the juridical understanding of the crime of embezzlement in the position of a notary, the crime of embezzlement in the position of a notary for the use of money deposited from the sale and purchase of land, and judges' considerations regarding the decision of the Supreme Court Number 508 K/PID/2017 against a notary who committed a crime of embezzlement. This study used a statutory research approach and a case approach, with a normative juridical type of research. The data analysis technique used the descriptive analysis method and legal interpretation. The study results showed that embezzlement in positions as regulated in Article 374 of the Criminal Code was a serious crime of embezzlement due to employment, position, and salary relationships. The Supreme Court's decision Number 508 K/PID/2017 had fulfilled the elements of embezzlement. If they receive money deposited, notaries must comply with the provisions in Article 1694 to Article 1739 of the Civil Code. The judge's consideration in imposing a crime against a notary who committed embezzlement in the office was based on the indictment, statements of witnesses and defendants, and evidence.